2016
DOI: 10.1186/s40101-016-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and geographic insights into the distinct gut microbiota in elderly women from two different geographic locations

Abstract: BackgroundA large number of microorganisms reside within the gastrointestinal tract, especially in the colon, and play important roles in human health and disease. The composition of the human gut microbiota is determined by intrinsic host factors and environmental factors. While investigating environmental factors to promote human health is of great interest, few studies have focused on their effect on the gut microbiota. This study aimed to investigate differences in gut microbiota composition according to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…PCA based on genus compositions showed that the P. spinosa gut microbial communities could be distinguished at the third axis (Figure b). This result indicated that the compositions of the P. spinosa gut microbial communities showed geographical differences, consistent with previous reports in other hosts (Bletz et al., ; Escobar, Klotz, Valdes & Agudelo, ; La‐ongkham, Nakphaichit, Leelavatcharamas, Keawsompong & Nitisinprasert, ; Ni, Yan, Yu & Zhang, ; Shin, Sim, Lee & Shin, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…PCA based on genus compositions showed that the P. spinosa gut microbial communities could be distinguished at the third axis (Figure b). This result indicated that the compositions of the P. spinosa gut microbial communities showed geographical differences, consistent with previous reports in other hosts (Bletz et al., ; Escobar, Klotz, Valdes & Agudelo, ; La‐ongkham, Nakphaichit, Leelavatcharamas, Keawsompong & Nitisinprasert, ; Ni, Yan, Yu & Zhang, ; Shin, Sim, Lee & Shin, ).…”
Section: Resultssupporting
confidence: 91%
“…The gut microbiota of P. spinosa was collected from approximately 0.3-g samples of the hindgut of each individual. CCGM, gut microbiota from six cultured P. spinosa individuals from Cili; CWGM, gut microbiota from five wild P. spinosa individuals from Cili; JCGM, gut microbiota from five cultured P. spinosa individuals from Jing'an; JWGM, gut microbiota from six wild P. spinosa individuals from Jing'an; CWMM, freshwater microbiota from the habitat of wild P. spinosa from Cili; CCIWM, inflow water microbiota from a cultured pond in Cili; CCOWM, outflow water microbiota from a cultured pond in Cili; JWWM, freshwater microbiota from the habitat of wild P. spinosa from Jing'an; JCIWM, inflow water microbiota from a cultured pond in Jing'an; JCOWM, outflow water microbiota from a cultured pond from Jing'an [Colour figure can be viewed at wileyonlinelibrary.com] Klotz, Valdes & Agudelo, 2014;La-ongkham, Nakphaichit, Leelavatcharamas, Keawsompong & Nitisinprasert, 2015;Ni, Yan, Yu & Zhang, 2014;Shin, Sim, Lee & Shin, 2016).…”
Section: Resultsmentioning
confidence: 99%
“… 24 , 25 Environmental factors, including diet, lifestyle, hygiene, antibiotic treatment, and probiotics, also contribute to the alteration of the intestinal microbiota composition. 26–31 Notably, the effects of diet and antibiotics on the intestinal microbiota also depend on the host genetic background. 32 , 33 …”
Section: The Intestinal Microbiota and Its Regulatorsmentioning
confidence: 99%
“…In contrast, all three geographical locations (Europe, North America, and Central America) were significantly different to one another in studies that sequenced the V4 hypervariable region. Other studies have independently identified geographical location as a factor in community structure, one sequencing the V4 region [30] and the other the V1-V2 hypervariable region [86]. Children from Western geographical areas had a similar microbiome structure at the phylum level.…”
Section: S Rrna Sequencing Region and The Microbiomementioning
confidence: 99%